EVALUATION OF OCHRATOXIN A IN Theobroma cacao L. "trinitario cacao", BY HIGH-EFFICIENCY LIQUID CHROMATOGRAPHY (HPLC) AND MICOTOXYGENIC ANALYSIS DURING THE PROCESS OF HARVESTING, FERMENTATION, DRYING AND STORAGE - Ramos, Norma (2018)
The presence of ochratoxin A (OTA), a mycotoxin with carcinogenic properties, was analyzed in the beans of Theobroma cacao L. "trinitario cacao" from the collection center of Pisana-Tingo Maria, of the San Martin Region, Peru. The samples were collected in four stages of production: harvesting, fermentation, drying and storage. The OTA was extracted using 60 % acetonitrile and purified by immunoaffinity columns and subsequent quantification by high performance liquid chromatography (HPLC). The recovery percentage of the method used was evaluated by using samples fortified with OTA, showing a recovery percentage greater than 95 %. The beans evaluated in the different stages of production did not show the presence of ochratoxin A and in the mycotoxigenic analysis the presence of fungi of the genus Fusarium, Penicillium and yeasts was evidenced.